2021
DOI: 10.2166/wst.2021.200
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and efficacy studies of Laccase immobilized on Zein-Polyvinyl pyrrolidone nano fibrous membrane in decolorization of Acid Red 1

Abstract: Azo dyes are widely used in textile industries. A significant portion of these recalcitrant dyes are being discharged to the natural waters. Due to their low biodegradability they pose serious pollution problems if untreated. In this work, decolourization studies of Acid Red 1 (AR1) by laccase enzyme immobilized onto Zein – Polyvinyl pyrrolidone composite nanofiber is done. The nanofibers were characterized by SEM and FTIR analysis. pH and temperature profiles of immobilized enzyme were found to be broader tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
(37 reference statements)
1
4
0
Order By: Relevance
“…Small peaks at 2872, 647, and 576 cm -1 which were absent in PLA; however, available in PVP pointed out that there was an association between PLA and PVP. These peaks are also in accordance with the studies of Ranimol et al (2021) who reported similar results for neat PVP. A slight shift was noted in the peak from 1269 cm -1 to 1291 cm -1 upon essential oil incorporation to the PLA-PVP fiber.…”
Section: Ir-spectra Of the Fibrous Webssupporting
confidence: 93%
“…Small peaks at 2872, 647, and 576 cm -1 which were absent in PLA; however, available in PVP pointed out that there was an association between PLA and PVP. These peaks are also in accordance with the studies of Ranimol et al (2021) who reported similar results for neat PVP. A slight shift was noted in the peak from 1269 cm -1 to 1291 cm -1 upon essential oil incorporation to the PLA-PVP fiber.…”
Section: Ir-spectra Of the Fibrous Webssupporting
confidence: 93%
“…Therefore, storage stability becomes a crucial factor to be credited when designing a robust biocatalyst 47 . Thus, it is expected that the heterogeneous biocatalysts maintain their catalytic activity even over the days of storage 84 . In this study, the immobilized and free laccase stability was measured from storage at 5°C for 30 days.…”
Section: Resultsmentioning
confidence: 99%
“…47 Thus, it is expected that the heterogeneous biocatalysts maintain their catalytic activity even over the days of storage. 84 In this study, the immobilized and free laccase stability was measured from storage at 5 C for 30 days. Figure 8 shows the performance of the tested two enzymes.…”
Section: Storage Stabilitymentioning
confidence: 99%
“…However, the decolorization was affected when temperature and pH were increased up to a certain level. It led to enzyme inactivation due to high temperature and the dispersion of dye molecules across the matrix due to the increase in pH (Ranimol et al 2021). The decolorization increases with the time duration and equilibrium was sorted out and the temperatures above 40 o C inhibit the enzyme activity leading to diminishing the decolorization (Iqbal et al 2021).…”
Section: Dye Decolorization Box-behnken Methodsmentioning
confidence: 99%